A reconsideration of the fossil Suidae of the Makapansgat Limeworks, Potgietersrus, Northern Transvaal - Bender, Patrick Alan (My University, 2016)
The prcesen.tstudy examinee all the fully prepared Maka~ansgat Limeworks' fossil suid sped1l1p..l1s. Thirty undescribed and three uneatalogued 'spe~imell~' were ad{~g to the previously'dt'tcdttl,Q. ,; .h-· ..~ ,cpUectiqp. The 'b:anial, morphology of these suids is compared to the extant southern African- Suk.<ie, Potamochoeru« porcus (bushpiib and, Fh~coChoern$ f~tMopic~s(warthog), and oth~r, relevant extant ~ - ~ and fossil genera, .A sys~ern of measurements was ,(ed to .facilitate tile~des'Criptl6nand analysis of the .~) LimeWotks fgssils and in the cbtiiparisous with the other snids, 0 () It (I \\ f, " :the ta:xonJ~y and phylogeny of the Lhneworks spe('Jes Potamocho5Jides shawi is revised, It is shown "to be di$~inct from Mctridiocl;oetys andrews/:. AD cladogratn.;illustratblg (he crplationships betWeen ~\ f) c» specific Pllo-Pleistocene African. suid genera is pres~nted, and iIi is concluded that Potampcltr~~roides is ;.l~ 0". ~ (I.. '. _/?_ -,l) c-, more primitive and therefore possibly Older than previously thought. Since Potamoc1toeroidt!s"ana th~ '() Makapansgat hominid rema!ijs occur in the same geological unit, it is suggested that Australopitllecus o (I , . (,) . , ajriccmus, may also be older than previously considered. I) (1 " .. ,':-:::;z"\.:- .. _ _ ' .' _ _ .o'_ .' 0 The pruaeoec\'}logy,and taphonomy of the Limeworks Suidae is examined and discussed. Indlcntions q, ) ar,~ that the suMs were brought into the cave mainly by predators, "including hyaenas, {~Pds'and the " if';" hominidAuttralOj)itllecut a!ncamls. o ~)", ~ ~\ (I o o (( o D 0' o () o ',) ;';_'! II (_{ (/ " In an 014 hut with a tin roof on a univer~ity campus inJohannesburg, a magician presides over a room [) full of bones. Row upon toW of mandibles, femurs, ~')ose teeth, and. horn cores lie' on shelves and trestle tables, are neatly arranged in drawers, or overflow rotc .wooden boxes on the flo~f' There are " \j tens of thousands of skeletqI fragments, all neatly "numbered • the remains of more antelope, pig, and " giraffe than anyone has seen together since the time of the great migrations. The bones are suprislngly (:i heavy. Eac.~has lain so long beneath the earth that all its cells have been replaced by calcite or silica. \\. ". .\" c Soil stp[f has seeped into the::tissue; keeping its precise shape, but taking its place, turning it into c)j li:mestop~•.;J'hey/tre all fgssUs, roWs of Gone turned to stone by time, "(Watson 1982, p6).
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. March, 1990.